The median effective analgesic concentration of ropivacaine in ultrasound-guided interscalene brachial plexus block after arthroscopic rotator cuff repair - Xu, Cheng; Gu, Fei; Liu, Yang; Chen, Rui; Wang, Chengyu; Lu, Jie (Frontiers in Pharmacology, 2022)
Background: The median effective analgesic concentration (MEAC) of ropivacaine in interscalene brachial plexus block (ISBPB) for postoperative analgesia after arthroscopic rotator cuff repair (ARCR) has not been determined. Therefore, this study aimed to evaluate the MEAC after ARCR using 10 mL ropivacaine. Method: This study was conducted on 40 patients with American Society of Anesthesiologists grade I or II who had selective ARCR. The 10 mL ropivacaine was administered for determined, with an initial concentration of 0.3% using up-and-down sequential allocation. After successful or unsuccessful postoperative analgesia, the concentration of ropivacaine was decreased or increased by 0.05% in the next patient. We defined successful postoperative analgesia as a visual analog scale score of <4 at rest within the initial 8 hours after ISBPB. The analytic techniques of linear, linear-logarithmic, exponential regressions and centered isotonic regression were used for calculating MEAC. The secondary outcomes was sufentanil consumption, time to 1st rescue analgesic, onset time of sensory block and motor block. Results: The concentration of ropivacaine administered ranged from 0.1% to 0.35%. The MEAC from the four different methods (linear, linear-logarithmic, exponential regressions and centered isotonic regression) were 0.207% (95% CI, 0.168–0.355%), 0.182% (95% CI, 0.165–0.353%), 0.196% (95% CI, 0.154–0.356%), and 0.163%, respectively. Of the four models, exponential regression had the least residual standard error (0.0990). Conclusion: The MEAC derived from the four statistical models for 10 mL ropivacaine in ultrasound-guided ISBPB for postoperative analgesia was distributed within a narrow range of 0.163%–0.207%. The exponential regression model calculated by the goodness-of-fit test at a concentration of 0.196% best fits the study data.